Fine woodworking best tips on finishing, sharpening, gluing, storage, and more (The Taunton Press, 2011)
Suitable for woodworkers of different skill levels, this book offers over 300 tips and techniques, from storage solutions and surface preparation; to milling lumber and power-tool strategies; and, to insights into clamping, gluing, sharpening, finishing and more